2007
DOI: 10.1196/annals.1415.031
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Distribution of Thymosin β4

Abstract: The localization of Oregon Green cadaverine-labeled thymosin beta(4), its fragments, and variants was investigated in cytoplasm-depleted A431 cells and in microinjected cells without and with fixation. The studied thymosin beta(4) variants included substitutions of the lysine residues within the basic cluster (14-KSKLKK-19) and the actin-binding motif (17-LKKTETQ-23). In contrast to Oregon Green cadaverine, none of the variants or fragments of thymosin beta(4) could pass the intact nuclear pore of cytoplasm-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…According to this study, the Tβ4 cytoplasmic-nuclear diffusion might be due to changes in the barrier function of the nuclear pores [17].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…According to this study, the Tβ4 cytoplasmic-nuclear diffusion might be due to changes in the barrier function of the nuclear pores [17].…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, a passive but regulated diffusion has been proposed as the mechanism that could explain the ability of Tβ4 to shuttle into the nucleus [17]. According to this study, the Tβ4 cytoplasmic-nuclear diffusion might be due to changes in the barrier function of the nuclear pores [17].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Tβ protein family has a relatively conserved motif ‘LKKTET’ involving Tβ binding to actin [29], [30]. Interestingly, through bioinformatics analysis, it is found that BmTHY also has a relatively conserved motif ‘LKHTET’ with only one amino acid difference from ‘LKKTET’.…”
Section: Discussionmentioning
confidence: 99%
“…BmTHY was found mostly in the nucleus but was also observed in the cytoplasm. Some actin-binding proteins have been previously reported to localize intracellularly to or shuttle into the nucleus [30], [40], [41], [42]. For example, Huff [40] reported that Tβ4 served as a G-actin sequestering peptide in the nucleus and was specifically translocated into the cell nucleus by an active transport mechanism, requiring an unidentified soluble cytoplasmic factor.…”
Section: Discussionmentioning
confidence: 99%